A practical approach to the development of English education in remote areas of China enabled by AI technology - Li, Jialing; Ren, JieYing (IC-ITECHS, 2024)
With the development of economic globalization, the international status of English is becoming increasingly prominent. Especially in remote areas, the need for English basic education is more urgent. In recent years, the innovation of AI technology has promoted the development of higher quality English education in remote areas, including personalized English learning, intelligent English tutoring system, virtual English learning environment and so on. In the issue of AI-enabled English education, whether it is the technology itself, or the cultivation of ideas and methods, it is global. Therefore, it is necessary to form broader, more comprehensive and deeper cooperation on the network platform on a global scale to promote large-scale innovative talent training.